Influence of psychological stress and coping styles in the professional identity of undergraduate nursing students after the outbreak of COVID‐19: A cross‐sectional study in China - Yanyan Zhao; Qiang Zhou; Jie Li; Jiage Luan; Bingfei Wang; Yan Zhao; Xinru Mu; Haiying Chen (Wiley, 2021)
Abstract Aim To investigate the influencing factors in professional identity of undergraduate nursing students after the outbreak of COVID‐19. Design Cross‐sectional study. Methods The study covered 2,999 nursing students in six undergraduate nursing schools. Several self‐report questionnaires were used to collect the general information, psychological stress, coping styles and professional identity of the undergraduate nursing students. Results The overall average score of the professional identity of nursing students (3.67 ± 0.51) has increased significantly after the outbreak of COVID‐19. The professional identity of the undergraduate nursing students was negatively correlated with psychological stress (r = −0.23, p < .001), expectation (r = −0.12, p < .001) and avoidance (r = −0.16, p < .001), but was positively correlated with solving problems (r = 0.18, p < .001) and seeking support (r = 0.12, p < .001). Academic performance, positions, grades, reasons for choosing a nursing profession, parents or relatives engaged in nursing work and the risk degree of residence were the factors influencing the professional identity score of undergraduate nursing students' (p < .001).